2007
DOI: 10.1007/s00383-007-1912-z
|View full text |Cite
|
Sign up to set email alerts
|

Atypical aphallia

Abstract: Aphallia is a rare genital anomaly poorly reported in literature. The authors describe an atypical case of aphallia characterized by ultrasound and magnetic resonance imaging findings of atrophic cavernous corpus associated with anterior urethral opening. Aphallia is a complex malformation, featuring various anomalies which should be assessed before electing a specific treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…The HCG challenge test is necessary because it shows the presence of a functional testicle. Other studies about profile hormones found that testosterone, LH/FS, AMH, 17 hydroxyprogesterone, 4 androstenedione, inhibin B, Dihydrotestosterone (DHT), 5alpha-reductase androgen receptors within normal limits in aphallia (El-Qadiry et al, 2020;Bahe et al, 2016;Coquet-Reinier et al, 2007). The presence of all these hormones is like a fertile man, due to the presence of normal testicles like two patients in this review have a normal level of testosterone, prolactin, estradiol, LH FSH.…”
Section: Discussionmentioning
confidence: 59%
“…The HCG challenge test is necessary because it shows the presence of a functional testicle. Other studies about profile hormones found that testosterone, LH/FS, AMH, 17 hydroxyprogesterone, 4 androstenedione, inhibin B, Dihydrotestosterone (DHT), 5alpha-reductase androgen receptors within normal limits in aphallia (El-Qadiry et al, 2020;Bahe et al, 2016;Coquet-Reinier et al, 2007). The presence of all these hormones is like a fertile man, due to the presence of normal testicles like two patients in this review have a normal level of testosterone, prolactin, estradiol, LH FSH.…”
Section: Discussionmentioning
confidence: 59%
“…B.C. Reiner et al, 2007 [ 28 ] Neonate, H-2, GA 39 weeks - Ambiguous genitalia • The physical examination demonstrated a well-developed male with a rudimentary genital bud (5 mm length). • The voiding cystography: Demonstrated bilateral grade II vesicoureteral reflux, normal bladder and posterior male urethra.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of cases involve males with 97% (n:40) of all cases (1–3,7–29), and 2% (n:1) was female [ 2 ]. Of the 35 cases, the majority with 48% (n:20) cases were term neonates [ 2 , 3 , 8 12 , 14 , 17 , 18 , 21 , 22 , 25 , 28 , 30 , 33 ], while 19% (n:8) were preterm neonates [ 2 , 13 , 24 , 26 , 32 , 34 ], 9% (n:4) were infants [ 1 , 16 , 25 , 34 ], 9% (n:4) were under five [ 5 , 7 , 19 , 27 ],and 12% (n:5) were over 5 years old [ 6 , 15 , 23 , 29 , 31 ]. The patient with the lowest gestational age was 31 weeks [ 13 ], with the oldest patient ‘s age was 31 years old [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aphallia should be differentiated from concealed penis, rudimentary penis, micropenis, epispadias, hypospadias, intrauterine amputation of the phallus, and pseudohermaphroditism [10]. Diagnosis can be established by careful clinical examination, karyotyping, and radiologic investigations including cystography, and magnetic resonance imaging that can help in the anatomical interpretation of complex genital anomalies and can guide further management [11,12].…”
Section: Discussionmentioning
confidence: 98%